Inverse colloidal crystal membranes for hydrophobic interaction membrane chromatography. Issue 18 (15th September 2015) - Wenz, Christian; Barbas, Coral; López‐Gonzálvez, Ángeles; Garcia, Antonia; Benavente, Fernando; Sanz‐Nebot, Victoria; Blanc, Tim; Freckleton, Gordon; Britz‐McKibbin, Philip; Shanmuganathan, Meera; de l′Escaille, Francois; Far, Johann; et al.
Abstract : J. Sep. Sci. 2015, 38, 3262‐3270 DOI:10.1002/jssc.201500551 This cover picture illustrates an inter‐laboratory study on the robustness and portability of capillary electrophoresis‐mass spectrometry that is presented in this issue. Thirteen independent laboratories located around the globe as indicated on the map were participating in this study. The sheath‐flow capillary electrophoresis‐mass spectrometry interface used by most participating groups is depicted schematically on the right hand side. Migration time, peak height and peak area of 10 representative target peptides of a trypsin‐digested protein sample were determined by every laboratory. The figures in the middle and left hand side show the final results obtained for means, repeatability (precision within a laboratory) and reproducibility (precision between laboratories). This study demonstrates that capillary electrophoresis‐mass spectrometry is robust enough to allow a method transfer across multiple laboratories and should promote a more widespread use of this technology in biopharmaceutical analysis and related fields.